Aminobisphosphonates reactivate the latent reservoir in people living with HIV-1 - Sanz, Marta; Weideman, Ann Marie K.; Ward, Adam R.; Clohosey, Matthew L.; Garcia-Recio, Susana; Selitsky, Sara R.; Mann, Brendan T.; Iannone, Marie Anne; Whitworth, Chloe P.; Chitrakar, Alisha; Garrido, Carolina; Kirchherr, Jennifer; et al. (Frontiers in Immunology, 2023)
Antiretroviral therapy (ART) is not curative due to the existence of cellular reservoirs of latent HIV-1 that persist during therapy. Current research efforts to cure HIV-1 infection include "shock and kill" strategies to disrupt latency using small molecules or latency-reversing agents (LRAs) to induce expression of HIV-1 enabling cytotoxic immune cells to eliminate infected cells. The modest success of current LRAs urges the field to identify novel drugs with increased clinical efficacy. Aminobisphosphonates (N-BPs) that include pamidronate, zoledronate, or alendronate, are the first-line treatment of bone-related diseases including osteoporosis and bone malignancies.Here, we show the use of N-BPs as a novel class of LRA: we found in ex vivo assays using primary cells from ART-suppressed people living with HIV-1 that N-BPs induce HIV-1 from latency to levels that are comparable to the T cell activator phytohemagglutinin (PHA). RNA sequencing and mechanistic data suggested that reactivation may occur through activation of the activator protein 1 signaling pathway. Stored samples from a prior clinical trial aimed at analyzing the effect of alendronate on bone mineral density, provided further evidence of alendronate-mediated latency reversal and activation of immune effector cells. Decay of the reservoir measured by IPDA was however not detected. Our results demonstrate the novel use of N-BPs to reverse HIV-1 latency while inducing immune effector functions. This preliminary evidence merits further investigation in a controlled clinical setting possibly in combination with therapeutic vaccination.